2021
DOI: 10.1096/fj.202002325rr
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A is an endogenous ligand for the triggering receptor expressed on myeloid cells‐2 (TREM2)

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Besides ACE2, other molecules seem to participate in SARS‐CoV‐2 infection, 7 including several molecules that might be involved in SARS‐CoV‐2 cell susceptibility, such as Neuropilin 1 and cluster of differentiation 147 (CD147), cyclophilin A, reported to be associated with enhanced viral infection 8–12 …”
Section: Introductionmentioning
confidence: 99%
“…Besides ACE2, other molecules seem to participate in SARS‐CoV‐2 infection, 7 including several molecules that might be involved in SARS‐CoV‐2 cell susceptibility, such as Neuropilin 1 and cluster of differentiation 147 (CD147), cyclophilin A, reported to be associated with enhanced viral infection 8–12 …”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, the identification of endogenous ligands of TREM2 has proven elusive although there is an emerging pattern of evidence suggesting that the receptor can interact with a wide array of negatively charged molecules mostly associated to tissue damage or cellular stress [ 19 22 ]. Except for the reports on the binding of the ubiquitous protein cyclophilin A [ 23 ] and a X-ray crystallography model of TREM2 centered on a prominent surface of positively charged residues [ 24 ], most studies are related to the affinity of putative ligands with the receptor [ 11 ]. For this reason, in order to test the binding of SULF A to TREM2, we used a consolidated TREM2-reporter cell line that transduces receptor engagement by synthesis of GFP [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The downstream cascade signal of TREM2 is mediated by the electrostatic interaction with DNAX-activation protein 12 (DAP12) [ 11 , 13 ] that, upon phosphorylation, recruits SYK and initiates the intracellular pathway. The next steps are not fully elucidated but independent authors reported that TREM2-mediated activity depends on NFAT [ 20 , 26 , 27 ], a family of five transcription factors which are mostly regulated by Ca 2+ . In striking contrast to the response to C-type lectins, such as dectins or mincle, that requires NFAT together with canonical and non-canonical pathways of nuclear factor-B (NF-kB) in DCs and macrophages [ 28 ], 28 ], TREM2 signaling transduction is independent of NF-κB in DCs [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The downstream cascade signal of TREM2 is mediated by the electrostatic interaction with DNAXactivation protein 12 (DAP12) [11,13] that, upon phosphorylation, recruits SYK and initiates the intracellular pathway. The next steps are not fully elucidated but independent authors reported that TREM2-mediated activity depends on NFAT [17,21,22], a family of ve transcription factors which are mostly regulated by Ca 2+ . In striking contrast to the response to C-type lectins, such as dectins or mincle, that requires NFAT together with canonical and non-canonical pathways of nuclear factor-kB (NF-kB) in DCs and macrophages [23][24], TREM2 signaling transduction is independent of NF-kB in DCs [25].…”
Section: Transcriptional Regulation Of Intracellular Trem2 Signaling By Sulf Amentioning
confidence: 99%